Concept of the “Minimum Energy Expenditure” Principle (London Journal of Research In Science: Natural and Formal, 2025)
This paper reveals the concept of the “minimum energy expenditure” principle, which is one of the fundamental principles in the biological world. It plays a significant role in speciation, the formation of biodiversity, trophic chains, ecological niches, as well as in ensuring the long-term existence of biological species, populations, and individual organisms. The central idea of this principle is that among many possible scenarios, the one that requires the least energy expenditure for its continued existence is chosen. This, in turn, provides the selected scenario with a minimum of entropy, that is, maximum certainty. This regularity is characteristic of all established biological objects and processes. This generalized principle applies to a wide range of biological phenomena—from low-molecular processes to the biospheres level—and is one of the fundamental properties of open systems.
Keywords: speciation; Biodiversity; Principle of Minimum Energy Expenditure; Open Systems; Dissipative Structures; Trophic Chain; ecological niches; evolutionary optimization; energy efficiency in biology; reduction of entropy.